Morphogenetic development of trochlear groove and thigh muscles from embryo to fetus in humans - Aoi Ishikawa; Momoko Nagai-Tanima; Kanon Ishida; Hirohiko Imai; Akio Yoneyama; Shigehito Yamada; Hiroki Otani; Tomoki Aoyama; Tetsuya Takakuwa (PLoS ONE, 2026)
Mechanical forces caused by fetal movements are essential for normal musculoskeletal development. However, the relationship between skeletal development and knee joint motion in utero remains unclear. We aimed to clarify the development of lower limb musculoskeletal structures during the embryonic and early fetal stages from a kinematic perspective and to compare muscle and skeletal developmental processes. We analyzed 29 human embryonic and fetal specimens. Using phase-contrast X-ray computed tomography and magnetic resonance imaging, we analyzed the morphogenesis of the knee joint components, trochlear groove angle, and hypothetical joint motion of the thigh muscles in three dimensions. To analyze chronological morphogenesis, Procrustes analysis was performed, and Principal component analysis and linear discriminant analysis were subsequently conducted using the Procrustes coordinates. The trochlear groove angle on the plane vertical to the femoral axis decreased from approximately 160° to 130° until 120 mm Crown-rump length (CRL) and remained constant until 185 mm CRL. All hypothetical joint motions increased slowly between 30 and 100 mm CRL, whereas rapidly after approximately 100 mm CRL. The protrusions of the lateral femoral condyle became more pronounced from fetal stage as they grew. The timing of the onset of fetal movement and the increase in muscle mass and joint motion during early pregnancy were consistent with those of previous studies, and the timing of the angle stabilization occurred almost simultaneously with the rapid increase in femoral muscle mass and hypothesized joint motion. It suggested that stabilization of joint morphology enables smooth joint motion, which leads to an increase in muscle mass and joint motion.